Rumen degradable nitrogen inclusion in a native pasture diet for weaner goats - Kuswandi .; Muchji Martawidjaja; Zulbardi Muhammad; Bambang Setiadi; Didi Budi Wiyono (Jurnal Ilmu Ternak dan Veteriner, 2000)
A complete block design was applied to employ 40 weaner goats, initial weighing average of 14.6 kg, which were grouped into 5 supplementary treatments, i.e. 125, 250, 300, 350 dan 400 g of skim milk/d. Each animal received.1.25 kg gliricidia leaves. Mixed pasture was consumed freely. The research was conducted in Tanjungrejo village, Tongas district, Probolinggo. A digestibility study was conducted for 7 days. Measurements included nutrient intakes and digestibilities, liveweight gain, and feed conversion ratio. Data were analyzed using the GLM procedure of SAS (SAS, 1986). The results showed that the medium skim milk level (300 g/d) gave the highest dry component digestibility. Cell wall digestibility from the group given 125-300 g skim milk/d was higher (P<0.05) than those given 350-400 g/d. No significant (P>0.05) difference in organic matter or protein digestibility was found among treatments. Supplementation with 350 g skim milk/d gave higher protein or digestible protein consumption (P<0.05), while supplementation with 125 g/d gave the best feed utilization efficiency. Levels at 125-250 g skim milk/d gave weight gain of about 65 g/d, while at more than 250 g gave 57 g/d or less. The best feed conversion ratio (7.8) was obtained in the group fed 125 g skim milk/d. In order to optimize microbial activity in the rumen, provision of slowly rumen degradable protein sources such as legumes, or rumen undegradable protein is of great importance.   Key words: Rumen degradable N, weaner goats, digestibility, average daily gain